DETERMINATION OF BORAX CONTENT IN VARIOUS FOOD MATERIALS CIRCULATING IN AMBON CITY - Semuel Simra (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2025)
Food safety is a critical issue for public health, especially in developing countries like Indonesia, where the use of unauthorized food additives still occurs frequently. This study aims to analyze the presence of borax, or sodium tetraborate, in food circulating in Ambon City. The methods employed include qualitative analysis using turmeric paper and quantitative analysis through UV-Vis spectrophotometry. Out of 10 samples tested, 4 samples (40%) were positively detected to contain borax in the qualitative test. Quantitative analysis revealed borax concentrations ranging from 2.461 to 3.051 ppm, with the following details: Wayame Market Noodles (2.858 ppm), OM Supermarket Noodles (2.641 ppm), OM Supermarket Meatballs (2.935 ppm), and Mardika Market Meatballs (3.051 ppm). These findings indicate a serious health risk due to the consumption of borax-containing foods, which can lead to various health issues in both the short and long term.